2014
DOI: 10.1016/j.sbspro.2014.05.151
|View full text |Cite
|
Sign up to set email alerts
|

The Precautions to be Taken on the Faculties of Education to Improve Teacher Quality and to Increase Employment Opportunity

Abstract: The purpose of this study is to examine the Turkish education faculties on the areas of quantity and sufficiency of faculty members, student numbers, physical capacity, and the cultural environment to find the better and cost-effective solution to increase teacher's quality and their employment opportunity. One of the most important factors that affect teacher quality and employment opportunity is the national policy of education faculty and to raise teacher. The quality and quantity of education faculties hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…With the results of low intelligence quotient, it is very difficult for the Institute of Teacher Training and Education to produce graduates who have good quality. Dominant factors determining student achievement in school: (1) student characteristics (49%), (2) teachers (30%), and (3) others (21%) [24]. Hattie's study results are strengthened by another research result which showed that IQ had a contribution of 57.7% in the Biology learning achievement in High School students, 65.1% of intelligence quotient is positively related to learning success [25] and as many as 26.6% of student achievement was influenced by intelligence quotient.…”
Section: %mentioning
confidence: 99%
See 1 more Smart Citation
“…With the results of low intelligence quotient, it is very difficult for the Institute of Teacher Training and Education to produce graduates who have good quality. Dominant factors determining student achievement in school: (1) student characteristics (49%), (2) teachers (30%), and (3) others (21%) [24]. Hattie's study results are strengthened by another research result which showed that IQ had a contribution of 57.7% in the Biology learning achievement in High School students, 65.1% of intelligence quotient is positively related to learning success [25] and as many as 26.6% of student achievement was influenced by intelligence quotient.…”
Section: %mentioning
confidence: 99%
“…Teachers are the determining factor of education success [1][2][3]. Teachers contribution to education is very crucial, such as in the field of learning [4], student test results [5], form a socio-affective class structure [6], class communication and interaction [7].…”
Section: Introductionmentioning
confidence: 99%
“…The modern learning management systems are the systems that can accommodate an effective, efficient and directed management process on a measurable goal [4]. Furthermore, the process of applying learning management must be clearly described.…”
Section: Introductionmentioning
confidence: 99%